Pelatihan Pemanfaatan Media Sosial Untuk Kampanye Pencegahan Penyimpangan Perilaku Remaja di SMA Muhammadiyah 16 Jakarta - Khotimah, Wininda Qusnul; Agustini, Vilya Dwi; Tiara, Andys (Prisani Cendekia, 2024)
Behavioral deviations in the educational environment continue to increase and often adorn the news in various mass media. Actors and victims in this case involve children or adolescents. Adolescence is a period of Stress and Strain, in addition to the current era of communication and information technology which also makes it attached to social media. On this basis, this activity was carried out with the aim of being able to contribute to the understanding of deviations in adolescent behavior and the use of social media as a means of campaigning for the prevention of this, as well as an encouragement to create action in forming a means of handling and preventing violence in schools. The participants in this activity were IPM students of SMA Muhammadiyah 16 Jakarta. The training was conducted offline. This PkM material consists of; behavioral deviations, ranging from its forms to its impact on victims and the factors behind it to efforts that can be made to prevent and avoid it. Not only that, the PkM Team provided assistance to partners in making campaign materials regarding the prevention of behavioral deviations, especially in the school environment. This activity went well and smoothly, participants assessed that all material delivery could be understood, participants could also understand properly what behavioral deviations were and they were also motivated to be able to carry out behavioral deviation campaigns by utilizing medias.